Effects of different models of thermal conductivity on turbulent nanofluid flow through rectangular cavity in duct - Abdellahoum, Chahrazed; Mataoui, Amina; Abu-Hamdeh, Nidal; Öztop, Hakan Fehmi (Elsevier, 2015)
This article concerns the turbulent forced convection of nanofluids confined in a shallow cavity heated from all sides with a uniform temperature. This study aims to make a numerical analysis on the performance of a nanofluid composed of solid particles of alumina (Al2O3) dispersed in a base fluid (pure water) for various models of the thermal conductivity. The governing equations of the hydrodynamic flow and heat transfer are discretized by the finite volume method using a drawing power law. Numerical simulations are performed for a Reynolds number ranging from 4 x 10(4)-10(5) and a volume fraction of the nanoparticles between 0 and 0.04. The obtained results show that the heat transfer is enhanced with the studied parameters for all models of thermal conductivity. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Turbulent flow; Nanofluids; Thermal conductivity